My Schwannoma Vestibular. The day that my life changed - Juan Antonio Aznar (Universidad de Alicante, 2014)
The story describes the impact of a diagnosis on the author's life: Vestibular schwannoma (also known as acoustic neuroma). From that moment, all the quotidian, the relative quiet of the daily routine and the prioritization of needs experienced a substantial change in his life. The past and the future come together in a tight bunch of speculations about what was, is and will be his life after these new experiences, which emerge from a fundamental rethinking of the meaning of existence. The decision to narrate their experiences in this context contributes largely to self-reflection and, in turn, builds a narrative material that can help us reflect on situations similar to others.